Comparison of skiing time and vertical ground reaction force between the short turn and basic parallel turn during alpine skiing - Kim, J.-H.; Kim, J.-N. (Korean Journal of Sport Biomechanics, 2017)
Objective: This study aimed to investigate the differences in skiing time and vertical ground reaction force (vGRF) between the basic parallel turn and short turn. Method: Eleven alpine ski instructors (age: 28.73±4.29 yrs, height: 172.36±6.30 cm, body mass: 71.45±9.16 kg, career: 11.09±2.70 yrs) participated in this study. Each skier was asked to perform a basic parallel turn and short turn on a 16° groomed slope. A foot pressure measurement system was used to measure the skiing time and vGRF under the three plantar regions (forefoot, midfoot, rearfoot). Results: Skiing time decreased significantly in all three phases during the short turn (p<.05). In the initiation phase, the vGRF showed a greater decrease on the midfoot and rearfoot during the short turn (p<.05). In the steering phase 1, the vGRF showed a greater increase on the forefoot and decreased on the midfoot during the short turn (p<.05). In the steering phase 2, the vGRF showed a greater increase on the forefoot and rearfoot during the short turn (p<.05). Conclusion: Our findings proved that the skiing time and vGRF changed during the short turn. Consequently, we suggest that recreational skiers should decrease the skiing time of the steering phase compared to that of the initiation phase and increase the vGRF on the forefoot and rearfoot in the steering phase.